A Pedagogical Study of Akhlak in Habib Uthman bin Yahya’s Adab al-Insan - Syarif, Fajar (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2025)
This study on the akhlak education construct of Habib 'Uthmân bin Yaḥyâ aims to analyse Habib 'Uthmân bin Yaḥyâ's thoughts on akhlak education for the Arab community in Betawi. This study explores the life journey, works, and thoughts of Habib 'Uthmân bin Yaḥyâ as recorded in archives or books, journals, and newspapers related to Habib 'Uthmân bin Yaḥyâ in the context of his life history, including teaching akhlak education to the Arab community in Betawi. This research found that Habib 'Uthmân bin Yaḥyâ taught akhlak education to the Arab community to preserve the Hadrami community and reject akhlak values that conflicted with Hadrami customs and traditions. This qualitative research uses data sources such as books, journals, documents, and various other literature related to Habib 'Uthmân bin Yaḥyâ's akhlak education philosophy. The research employs hermeneutics in analysing data by interpreting texts or transforming ignorance into knowledge. This study on Habib 'Uthmân bin Yaḥyâ's akhlak education concludes that akhlak education is an active process. Students must possess cognitive abilities and affective and psychomotor skills, with akhlak attitudes and character ingrained within them.